Active Learning Methods and Technology: Strategies for Design Education. (October 2016) - Coorey, Jillian
Abstract: The demands in higher education are on the rise. Charged with teaching more content, increased class sizes and engaging students, educators face numerous challenges. In design education, educators are often torn between the teaching of technology and the teaching of theory. Learning the formal concepts of hierarchy, contrast and space provide the critical foundation of a design education. However, without learning the tools (technology) a student will struggle to bring their concept to fruition. This article proposes using active learning techniques, specifically peer learning, as an engaging method to augment teaching technology. Students participated in peer‐based exercises throughout the course of a semester, including technology teams, technology checklists and group software challenges. Observations and survey data conclude students comprehension of technology improved and the instructor was afforded time to spend on the teaching of theory and process. Peer learning fosters a collaborative learning community, increases leadership skills and creates lifelong learners. Although these methods were used in a design course, this study can serve as a model for other disciplines that integrate technology in the classroom or for educators seeking active learning methods.